Siadong Tuktuk Area: A Source of Inspiration for Artistic Expression - Tindaon, Clinton Dowira; Muslim, Muslim (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
By fostering growth in the areas of lodging, communication, and transportation, Indonesia's tourist industry contributes significantly to the country's economy. When tourism is managed well, it may raise living standards, spur economic growth, and generate employment possibilities. The Samosir Regency, especially the Tuktuk Siadong region, which is renowned for its rich Batak culture and breathtaking natural beauty surrounding Lake Toba, is one of the most intriguing instances. Tuktuk Siadong's traditional villages, indigenous homes, and lively cultural rites inspire artists, particularly painters, in addition to providing stunning scenery. The purpose of this study is to investigate how Tuktuk Siadong might serve as a source of inspiration for paintings as well as how it might advance local artistic and cultural preservation. The four primary phases of the creative process—preparation, elaboration, contemplation, and realization—follow a systematic methodology. Data collecting, conceptual development, artistic method experimentation, and painting execution are all part of these phases. Three of the twelve paintings produced as a result of this study are highlighted in this publication. With elements of traditional Batak symbols and natural sceneries, these artworks portray Tuktuk Siadong's scenic beauty and cultural diversity. The imaginative methods used, such chiaroscuro and bravura, add to the paintings' visual impact and lend them both artistic appeal and cultural relevance. In conclusion, the paintings help to introduce, promote, and protect Tuktuk Siadong's natural and cultural legacy. In addition to assisting people in appreciating Batak cultures, they emphasize the importance of visual arts in fostering cultural identity and tourism growth.